Gas hydrate formation rates from dissolved‐phase methane in porous laboratory specimens. Issue 16 (19th August 2013) - Waite, W. F.; Spangenberg, E.
Abstract [1] Marine sands highly saturated with gas hydrates are potential energy resources, likely forming from methane dissolved in pore water. Laboratory fabrication of gas hydrate‐bearing sands formed from dissolved‐phase methane usually requires 1–2 months to attain the high hydrate saturations characteristic of naturally occurring energy resource targets. A series of gas hydrate formation tests, in which methane‐supersaturated water circulates through 100, 240, and 200, 000 cm3 vessels containing glass beads or unconsolidated sand, show that the rate‐limiting step is dissolving gaseous‐phase methane into the circulating water to form methane‐supersaturated fluid. This implies that laboratory and natural hydrate formation rates are primarily limited by methane availability. Developing effective techniques for dissolving gaseous methane into water will increase formation rates above our observed (1 ± 0.5) × 10−7 mol of methane consumed for hydrate formation per minute per cubic centimeter of pore space, which corresponds to a hydrate saturation increase of 2 ± 1% per day, regardless of specimen size.